Periodontal status and treatment needs of primary school teachers in the absence of formal school oral health programme (2014)
Information is sparse about the periodontal health of teachers who play important: roles in prevention of oral diseases in schools. Especially in developing countries where the promotion of oral health in school programmes is still sub-optimal. The objective of the study was to evaluate the periodontal health status and periodontal treatment needs of primary school teachers in a country lacking formal school-based oral health programmes. This was a descriptive survey in which intraoral examination was conducted on 407 primary school teachers. Recordings on the oral hygiene status using OHI-S. bleeding on probing, periodontal pocketing and treatment needs with CPITN and tooth mobility were obtained by a trained and calibrated examiner. Information on socio-demographic characteristics was also sought. Data were analyzed using SPSS and the level of significance set atp<0.05. None of the teachers had healthy periodontium, 3 bled to probing, 284 had calculus accumulation and 109 had shallow pockets while 11 had deep periodontal pocketing. Majority (80.6%) of the teachers had poor oral hygiene and 43 (10.6%) had one or more mobile teeth. A higher proportion of rural based teachers had periodontal pockets compared to those in urban areas (38.5% vs. 26.7%. p = 0.026). Older teachers were more likely to have mobile teeth (p = 0.002). There were significant positive correlations between OHI-S, CPITN score and number of mobile teeth. Periodontal disease is highly prevalent among primary school teachers in the country with calculus accumulation being the predominant feature. The periodontal treatment need of most of the teachers is in the form of oral prophylaxis and non-surgical periodontal treatment